Corporate Social Responsibility PT. Pertamina Case Study: Gerakan Menabung Pohon - Ermasari, Elisa; Rudito, Bambang (Journal of Business and Management, 2014)
Indonesia is one of the countries that have the largest number of forest in the world. Indonesia had previously been named by the United Nations to be one of the largest oxygen producing countries in the world and into the lungs of the world. But now Indonesia has lost a lot of their forest. This was shown by the destruction of forests across Indonesia, and make Indonesia as one of the countries that has the fastest deforestation in the world. Global warming is one of the major problems that must be faced by all people in the world. Therefore PT. Pertamina seeks to find solutions to these problems and create a CSR (Corporate Social Responsibility) that aims to reduce the effects from global warming that has been faced by the world residents. Corporate social responsibility program from PT. Pertamina. This program is aimed to reduce the effects of global warming and want to improve the welfare of the people in East Lombok to check this program has been running smoothly or not, The author will analyze the relationship between each of the parties involved in implementing the "Gerakan Menabung Pohon" in Lombok Timur to see if the program has been able to show any results for the environment and local communities. To achieve the above objectives, the authors will use several independent theories literally community development, sustainable development, corporate social responsibility, and theoretical effectiveness of CSR programs to the community and the environment. And to get the results of this project the author uses a methodology, design research problem identification, data collection, data analysis and conclusions. And the result from this project is, the movements to plant 100 million trees by PT. Pertamina has contributed in reforestation in Indonesia and improve the welfare of the people. With this program, PT Pertamina already employs approximately 7200 farmers in the Lombok Timur.Keywords: global warming, go green, penghijauan di Indonesia, corporate social resposibility, gerakan menabung pohon, case study.